Evaluation of Personnel Information System Performance at the Department of Population and Civil Registration of Bengkayang Regency Using COBIT 5 - Linda, Tania; Wijaya, Agustinus Fritz (Journal of Information Systems and Informatics, 2021)
The Bengkayang Regency Population and Civil Registry Service is an institution that aims to record population administration data which includes data including birth data, marriage data and death data, identity cards, family cards, and children's identity cards. The Dukcapil Service Office is one of the services that serves the community, especially in population management. This study aims to refer to the version 5 COBIT framework for reviewing the management of Personnel SI at the Bengkayang Regency Population and Civil Registry Service. The domain used in COBIT 5 is "Monitoring, Evaluation and Assessment" (MEA). The results of the study determine the maturity of the Bengkayang Regent's Population and Civil Registry, and provide suggestions for the application of information technology to make it better in the future.
Keywords: Evaluate Performance; Information Systems; COBIT 5; MEA Domain